2020
DOI: 10.1016/s1003-6326(20)65307-9
|View full text |Cite
|
Sign up to set email alerts
|

Anodic process on Cu−Al alloy in KF−AlF3−Al2O3 melts and suspensions

Abstract: Inert anode development has been a topic of interest for decades. Cu-Al, Fe-Ni based alloys have shown promising results in low-temperature melts. Metallic anodes tend to contaminate the produced aluminium with their corrosion products and introducing alumina suspension particles in the electrolyte could resolve this problem by suppressing the convective transfer of corrosion products toward aluminium produced. In this paper, anodic processes on Cu-10Al electrode in molten KF-AlF3-Al2O3 (5 wt. %) and suspensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…133 Solheim suggested that the alumina particle size should be about 5 to 10 μm to promote the anode consumption of alumina. A similar conclusion was drawn by Yasinskiy et al 134 and Padamata et al, 25 where the alumina particle size should be around 5 μm. Moreover, they suggest that the alumina volume fraction in the electrolyte should be not more than 12 vol% for the proper functioning of the anode.…”
Section: Vertical Electrode Cellsupporting
confidence: 83%
See 2 more Smart Citations
“…133 Solheim suggested that the alumina particle size should be about 5 to 10 μm to promote the anode consumption of alumina. A similar conclusion was drawn by Yasinskiy et al 134 and Padamata et al, 25 where the alumina particle size should be around 5 μm. Moreover, they suggest that the alumina volume fraction in the electrolyte should be not more than 12 vol% for the proper functioning of the anode.…”
Section: Vertical Electrode Cellsupporting
confidence: 83%
“…Padamata et al investigated the effect of alumina volume fraction in KF-AlF 3 -Al 2 O 3 (CR = 1.3) melt on the electrochemical behaviour and oxides layers formed on the Cu 90 Al 10 anodes. 25 The anodic potential ranged between 2.5 and 3.5 V (vs Al/Al 3+ ) for a volume fraction between 0 and 15% for a current density of 0.4 A cm −2 at 750 °C. XRD results suggest the CuO and Cu 2 O phase concentration in the oxide layer with an increase in alumina volume fraction while the limiting current decreased.…”
Section: Inert Anode Materialsmentioning
confidence: 95%
See 1 more Smart Citation
“…Electrochemical behaviour of Cu-Al based alloys with compositions 86Cu-9Al-5Fe, 90Cu-10Al and 88.3Cu-10Al-1.7Be was tested in KF -AlF3 -Al2O3 melts and suspensions [41][42][43]. The influence of alumina volume fraction and the composition of anode were characterised by stationary and non-stationary polarization.…”
Section: Cu -Al Alloymentioning
confidence: 99%
“…Compared to ceramics and cermets, metallic anodes have shown promising results due to their high electrical conductivity, thermal shock resistance, robustness, ease of fabrication and easy electrical connectivity. 4 Cu-Ni-Fe [6][7][8][9][10] and Cu-Al [11][12][13] based alloys have extensively been studied in recent years in low-temperature electrolytes between 973 and 1123 K. This work is done in collaboration with Arctus Metals and IceTec in Iceland, who are developing an inert anode process. 10 The presence of Cu in the alloy is vital as the Cu oxides formed on the outer layer of the alloy prevent electrolyte penetration into the electrode.…”
mentioning
confidence: 99%